Cape Recife nature reserve - Meel, Photo: Ruchika (SA Heart Journal, 2025)
The original Portuguese name “Cape Recife” translates to “Cape of the reefs”, a reference to the geological features of this south-eastern part of South Africa’s coastline upon which many ships met their end.